Pembangunan Sistem Informasi Kenaikan Jabatan Fungsional Dosen Universitas Brawijaya - Muhammad Saifussolihin Putra Aditama; Satrio Agung Wicaksono; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The functional position of the lecturer is a position that shows the duties, responsibilities, authority and rights of a lecturer in a higher education unit which in its implementation is based on certain skills and is independent. The function of lecturer functional promotion is very important for the accreditation of universities where the lecturers take shelter. However, the process of lecturers functional improvement has a number of problems encountered in the process, namely the lecturer does not have his own initiative to make the promotion of functional positions and personnel employee overwhelmed in calculating the value of credit numbers. The development of information system of lecturer functional promotion is a solution to solve the problem. The method used is SDLC Prototyping method which includes user requirement identification, prototype creation, prototype testing, prototype improvement, and development of production version which hopefully can assist in designing this system. The result of this research is in the application of the system to overcome the problem of credit score calculation, resulting in the reduction of processing time to 5-10 minutes, and the application of the system to overcome the problem of the lack of lecturer's initiative result in automatic notification. From the results of system testing, obtained results of 100% valid of 17 test cases. Based on compatibility testing, the tested system is capable of running on various browsers.